Elaborating on modular interfaces in multi-provider contexts. Issue 9 (10th September 2020) - Peters, Vincent; Vähätalo, Mervi; Meijboom, Bert; Barendregt, Alice; Bok, Levinus; de Vries, Esther
Abstract : Purpose: This study examines how modular interfaces manifest in multi-provider contexts and how they can improve coordination and customization of services. The aim of the study is to describe interfaces in multi-provider contexts and elaborate on how they support the delivery of integrated patient care. Design/methodology/approach: A qualitative, multiple case study was conducted in two multi-provider contexts in healthcare services: one representing paediatric Down syndrome care in the Netherlands and one representing home care for the elderly in Finland. Data collection involved semi-structured interviews in both contexts. Findings: This study provides insight into several types of interfaces and their role in multi-provider contexts. Several inter- and intra-organizational situations were identified in which the delivery of integrated patient care was jeopardized. This study describes how interfaces can help to alleviate these situations. Originality/value: This study deepens the understanding of interfaces in service modularity by describing interfaces in multi-provider contexts. The multi-provider contexts studied inspired to incorporate the inter-organizational aspect into the literature on interfaces in service modularity. This study further develops the typology for interfaces in modular services by adding a third dimension to the typology, that is, the orientation of interfaces.